Partisipasi Masyarakat terhadap Perencanaan Saluran Irigasi di Kelurahan Kalase’rena Kecamatan Bontonompo Kabupaten Gowa - ., Imriyanti; M., Pratiwi; ., Nasruddin; ., Hartawan; S. A., Andi L.; A., Muh. Nurhalim (Faculty of Engineering UNHAS, 2025)
Community participation is very much needed in the development process of an area that requires the development of facilities needed by the community directly. The application of community participation in the Kalase'rena sub-district is processing the rice field irrigation system in the sub-district. It is known that this location has rice fields and plantations with a pumping system and a rain-fed irrigation system, because this sub-district is located in a highaltitude area. With these conditions, the welfare of the community is quite lagging behind. Through these conditions, solutions are needed to improve the welfare of the community, especially in the agricultural sector. To support this agricultural sector, an irrigation system or watering of rice fields is needed. The rice field irrigation system was created in stages; identifying areas, conducting location surveys, informing the public about the conditions of rice field irrigation. Then it continues with a system of exploring problems, analyzing the needs of the community/farmers and analyzing in the field both in terms of environmental conditions and the water sources needed. From this data, it is necessary to plan an irrigation canal system with direct management by the community and an open water canal system that can be monitored directly by the community. By planning a manual sluice system and open channels, the level of community satisfaction can be averaged at 79.2%, which really requires irrigation channels for irrigating rice fields in the Kalase'rena sub-district.